N‐methyliminodiacetic acid as a simple and highly efficient ligand for palladium‐catalyzed Suzuki–Miyaura cross‐coupling of aryl chlorides. (3rd February 2015) - Qi, Liang; Zhou, Xiuling; Li, Xiaogang; Li, Wei; Lv, Meiyun; Guo, Mengping
<x xml:space="preserve">Abstract</x> A simple, air‐stable, inexpensive and easily prepared molecule, N‐methyliminodiacetic acid (MIDA), is reported as a ligand for palladium‐catalyzed Suzuki–Miyauracross‐coupling reaction of phenylboronic acid with aryl chlorides. The yield of the corresponding Suzuki coupling reaction is up to around 90% at both high temperature of 80°C and room temperature under ambient atmosphere. Copyright © 2015 John Wiley & Sons, Ltd.